Exploring Social Media Use and Civic Engagement on the Discussion of Antinuclear Issue - Lin, Cathy S.; Kuo, Feng Yang; Hung, Ching Ya (International Journal for Applied Information Management, 2022)
Social media has brought a new communication revolution allowing users to connect, share, and discuss public & social opinions with others. The new look at social media has shaped social movements, and provides a fair voice to anyone who can be heard online. This research explores individuals’ civic engagement concerning the environmental issue of nuclear energy on social media. Nuclear energy is a global, social, and environmental issue, the research variables included in this study are self-presentation efficacy, fear of social isolation and stigma consciousness. The findings from this study will have implications for both research and practices, especially help understanding the civic engagement of social movement on social media.